Menstimulus Kemampuan Konstruksi Dan Eksplanasi Siswa Melalui Kombinasi Hands On Method Dan Flipped Classroom Pada Materi Gerak Lurus - Silvia Nadiana; Ngia Masta; Emi Darnah; Hana Bintang (Prosiding SNFA (Seminar Nasional Fisika dan Aplikasinya), 2020)
Abstract: The era of the industrial revolution 4.0 is an era where learning systems and science require innovative human resources. Therefore, the world of education is required to be able to evolve in the face of the industrial era 4.0, through a curriculum approach using the SCL (Student Centered Learning) method. SCL (Student Centered Learning) is a student-centered approach and is characterized by student activity in constructing and expanding their knowledge. Hands On Method integration (experiment based) in Flipped Classroom will motivate students to learn. This study aims to improve the students' construction and explanation skills through learning that applies a combination of Hands On Method and Flipped Classroom on straight motion material. The study was conducted at SMAN 37 Jakarta, using a quasi-experimental method with the Post-test Only Control Design research design. The population in this study were all students of class X MIPA SMA 37 Jakarta. Samples were taken by the control class (35 students of class X MIPA 2) and the experimental class (35 students of class X MIPA 4). Students in the experimental class were given treatment in the form of applying a combination of Hands On Method and Flipped Classroom on straight motion material. The results showed the average results of students' construction and explanation abilities in the experimental class with the application of the Learning model through a combination of hands on method and flipped increased by 83,57, with a maximum score of 100. Whereas for the control class with conventional methods was 77,85, with a maximum score of 90. This can also be seen from the graph of the percentage of students' answers to the ability of construction to increase by 85.7% and to the ability of expectations by 71.43%.Abstrak: Era revolusi industry 4.0 adalah Era dimana sistem pembelajaran dan ilmu pengetahuan membutuhkan sumber daya manusia yang inovatif. Karena itu, dunia pendidikan dituntut harus mampu berevolusi dalam menghadapi era industri 4.0, melalui sebuah pendekatan kurikulum menggunakan metode SCL (Student Centered Learning). Integrasi Hands On Method (berbasis eksperimen) pada Flipped Classroom akan memotivasi siswa dalam belajar.  Penelitian ini bertujuan untuk meningkatkan kemampuan konstruksi  dan eksplanasi siswa melalui pembelajaran yang menerapkan kombinasi Hands On Method dan Flipped Classroom pada materi gerak lurus.  Penelitian ini menggunakan  metode  kuasi eksperimen dengan desain penelitian Post-test Only Control Design. Populasi dalam penelitian ini adalah seluruh siswa kelas X MIPA SMA Negeri 37 Jakarta. Sampel yang diambil kelas control (35 orang siswa kelas X MIPA 2) dan kelas eksperimen (35 siswa  kelas X MIPA 4). Siswa pada kelas eksperimen diberi perlakuan berupa penerapan kombinasi Hands On Method dan Flipped Classroom pada materi gerak lurus. Hasil penelitian menunjukkan rata-rata hasil kemampuan konstruksi dan eksplanasi  siswa pada kelas eksperimen dengan penerapan model Pembelajaran melalui kombinasi hands on method dan flipped meningkat sebesar 83,57, dengan skor maksimum 100. Sedangkan untuk kelas kontrol dengan metode konvensional sebesar 77,85, dengan skor maksimum 90. Ini dapat dilihat pula dari grafik presentase jawaban siswa pada kemampuan konstruksi meningkat sebesar 85,7 % dan untuk kemampuan ekplanasi sebesar 71,43 %.